Control of band gaps of conjugated polymers by copolymerization - Cho, HN; Kim, DY; Kim, JK; Kim, CY (ELSEVIER SCIENCE SA, 1997)
Dihexylfluorenes have been coupled with a chemical unit such as vinylene, phenylene, vinylenephenylene or vinylenealkoxyphenylene to preserve conjugation in the alternating copolymers by employing the reactions of Heck, Suzuki and Wittig. All the copolymers display good photoluminescence (PL) and the PL spectra are broad to show vibronic structures as well as emission of the interchain excitons or excimers, except PDHFPP which shows a sharp PL spectrum. The broad spectra become sharp on dilution in chloroform to 10(-5) mol l(-1) due to a diminishing effect of the interchain excitons or excimers. The electronic state of polydihexylfluorene with the PL emission peak at 420 nm is changed to a lower-energy state when a vinylene or vinylene-para-phenylene unit is coupled to the alkylfluorene unit. The decrease in the energy state is pronounced when the two alkoxy units are attached to the phenylene unit to show the PL emission peak at 510 nm. However, no change in the electronic energy state is observed when a phenylene, vinylene-meta-phenylene or glycol-capped vinylenephenylene unit is coupled with the dialkylfluorene unit. (C) 1997 Elsevier Science S.A.